1997
DOI: 10.1046/j.1525-1497.1997.07118.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of two aspirin pretreatment regimens on niacin-induced cutaneous reactions

Abstract: An aspirin regimen of 325 mg is effective in suppressing niacin-induced cutaneous reactions. Increasing the dose to 650 mg does not provide additional benefit.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
46
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(47 citation statements)
references
References 15 publications
1
46
0
Order By: Relevance
“…Thus, to increase serum levels of HDL-C in patients with a moderate to high coronary risk is an important goal, whether or not LDL-C goals are achieved, since residual risks still persist. 44,46 Niacin (nicotinic acid) has antithrombotic effects associated with improvements in endothelial function and reduction of the inflammatory process in the vascular wall with stabilisation of the atherosclerotic plaque.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, to increase serum levels of HDL-C in patients with a moderate to high coronary risk is an important goal, whether or not LDL-C goals are achieved, since residual risks still persist. 44,46 Niacin (nicotinic acid) has antithrombotic effects associated with improvements in endothelial function and reduction of the inflammatory process in the vascular wall with stabilisation of the atherosclerotic plaque.…”
Section: Resultsmentioning
confidence: 99%
“…If, despite these measures, flushing still occurs, the use of 325 mg of acetylsalicylic acid 30 minutes before taking ER niacin may suppress or minimise its occurrence. 46 In practice, less frequent and intense flushes occur with continued use of niacin.…”
Section: Pharmacological Treatmentmentioning
confidence: 99%
“…However, despite complete suppression of niacin-evoked PGD 2 release by low doses of aspirin (81 mg/day), there are still signifi cant residual symptoms of fl ushing, even after pretreatment with higher doses (325 and 650 mg) ( 62,77,78 ) of aspirin which would suppress residual prostaglandin formation. A recent study has shown that aspirin only blocks vasodilation in hairy but not in glabrous skin ( 79 ).…”
Section: Effects On Hdlmentioning
confidence: 99%
“…Subject reports of flushing on a 100-mm visual analog scale were obtained Ϫ60, 0, 15, 30, 60, 90, 120, 180, and 240 min after administration of NA, as described in ref. 13. Measurements of cutaneous blood flow in the malar skin were also obtained in these subjects by using LDPI at 0, 20, and 45 min after the dose of NA.…”
Section: Measurement Of Na-induced Flushing Symptoms In Healthy Subjementioning
confidence: 99%